Dengue Hemorrhagic Fever Complicated With Hemophagocytic Lymphohistiocytosis in an Adult With Diabetic Ketoacidosis - Narayanasami, Ethayakumar (Cureus, 2020)
Dengue infection can cause a wide spectrum of presentations extending from simple self-limiting febrile illness to severe dengue, including dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Dengue associated hemophagocytic lymphohistiocytosis (HLH) is a rare, life-threatening condition characterized by the uncontrolled activation of macrophages and T cells, eliciting clusters of symptoms and signs and abnormal biochemical parameters. Herein we report a 28-year-old Sri Lankan female with no past medical history who presented with dengue hemorrhagic fever and diabetic ketoacidosis complicated with hemophagocytic lymphohistiocytosis. She was treated with a three-day course of intravenous methylprednisolone in addition to standard care for diabetic ketoacidosis and dengue hemorrhagic fever. She made an uneventful recovery.